DOMESTIC SOCIAL THOUGT ABOUT UNIQUENESS OF THE RUSSIAN MANAGERIAL ELITE - A. M. Amelina (Вестник университета)
The assessments of well-known Russian sociologists and philosophers (P. A. Sorokin, P. B. Struve, M. O. Menshikov) of one of the important features of the historical formation and existence of the Russian administrative elite – its national diversity have been analysed. The main characteristics and alternative estimates given by thinkers to this social phenomenon have been revealed. It has been shown that the main object of their attention is the question of whether the multinational elite is able to provide a qualitative level of management? In this issue, the points of view differ, so M. O. Menshikov took a negative position. The means that contribute, from the point of view of P.A. Sorokin and P.B. Struve, to creative development and integration of the interests of all subjects of multinational Russian society have been revealed in the article.